An Exergames Program for Adolescents With Type 1 Diabetes: Qualitative Study of Acceptability - Mak, Selene S.; Nally, Laura M.; Montoya, Juanita; Marrero, Rebecca; DeJonckheere, Melissa; Joiner, Kevin L.; Nam, Soohyun; Ash, Garrett I. (JMIR Diabetes, 2025)
Background: Numerous barriers to moderate to vigorous physical activity exist for youths with type 1 diabetes (T1D). The virtual exercise games for youth with T1D (ExerT1D) intervention implement synchronous support of moderate to vigorous physical activity including T1D peers and role models. Objective: This study aims to understand the acceptability of this intervention to participants. Methods: We conducted postprogram, semistructured, televideo interviews with participating youths to elicit perspectives on the acceptability of the intervention and experience with the program. Two coders independently reviewed and analyzed each transcript using a coding scheme developed inductively by senior researchers. Discrepancies were resolved by team discussion, and multiple codes were grouped together to produce 4 main thematic areas. Results: All 15 participants provided interviews (aged 14-19 years; 2 nonbinary, 6 females; median hemoglobin A1c level of 7.8% (IQR 7.4%-11.2%), 5 with a hemoglobin A1c level of ≥10%). Qualitative data revealed four themes: (1) motivation to engage in physical activity (PA)—improving their physical capabilities and stabilizing glucose levels were cited as motivation for PA and challenges of living with T1D were cited as PA barriers; (2) experience with and motivation to manage diabetes while engaging in PA—participants provided details of accommodating the inherent uncertainty or limitations of PA with diabetes and sometimes preparing for PA involved psychological and motivational adjustments while some relayed feelings of avoidance; (3) peer support encouraged engagement with the intervention—participants appreciated the peer aspects of components of ExerT1D and participants’ reflections of the facilitated group experience highlight many benefits of a small-group virtual program; and (4) improvements in PA and diabetes self-management efficacy—all participants credited the program with improving or at least raising awareness of T1D management skills. Conclusions: Our virtual PA intervention using an active video game and discussion component provided adolescents with T1D the confidence and peer support to engage in PA, improved awareness of diabetes-specific tasks to prepare for exercise, and improved understanding of the effect of PA on glucose levels. Engaging youths with a virtual video game intervention is a viable approach to overcome barriers to PA for adolescents with T1D. Trial Registration: ClinicalTrials.gov NCT05163912; https://clinicaltrials.gov/ct2/show/NCT05163912
Keywords: Computer science; Diabetes mellitus; Medicine; Preprint; Psychology; Qualitative research; Sociology; Type 2 diabetes; World Wide Web; dept.hms; peer-reviewed

Testing multiple delivery methods of the virtual exercise games for youth with T1D peer intervention: protocol development and feasibility - Ash, Garrett; Nam, Soohyun; Mak, Selene; Stults-Kolehmainen, Matthew; Haughton, Adrian; Turek, Carolyn; Baker, Julien; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth; et al. (Hormone Research in Paediatrics, 2026)
INTRODUCTION: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. METHODS: The program included 6 versions: study 1 (1.1-1.4) included an active video game, and study 2 (2.1-2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. RESULTS: Seventeen adolescents (median age 15.4 [IQR 14.6-16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%-11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min-90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = -1.12, 90% CI: [-1.78, -0.48]). CONCLUSIONS: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention's impact on engagement with physical activity, glycemic outcomes, and quality of life.
Keywords: Glycemic; Physical activity; Program evaluation; Protocol (science); Quality (philosophy); Quality of life (healthcare); dept.hms

Testing Multiple Delivery Methods of the Virtual Exercise Games for Youth with T1D Peer Intervention: Protocol Development and Feasibility - Ash, Garrett I.; Nam, Soohyun; Mak, Selene S.; Stults-Kolehmainen, Matthew; Haughton, Adrian D.; Turek, Carolyn; Baker, Julien S.; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth G.; et al. (Hormone Research in Paediatrics, 2026)
Abstract – Introduction: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. Methods: The program included 6 versions: study 1 (1.1–1.4) included an active video game, and study 2 (2.1–2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. Results: Seventeen adolescents (median age 15.4 [IQR 14.6–16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%–11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min–90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = −1.12, 90% CI: [−1.78, −0.48]). Conclusions: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention’s impact on engagement with physical activity, glycemic outcomes, and quality of life. © 2026 S. Karger AG, Basel
Keywords: Diabetes; Peer support; Physical activity; Type 1; Video games; dept.hms

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine